Role of L-Particles during Herpes Simplex Virus Infection - Heilingloh, Christiane S.; Krawczyk, Adalbert (Frontiers in Microbiology, 2017)
Infection of eukaryotic cells with α-herpesviruses results in the formation and secretion of infectious heavy particles (virions; H-particles) and non-infectious light particles (L particles). Herpes simplex virus type 1 (HSV-1) H-particles consist of a genome-containing capsid surrounded by tegument proteins and a glycoprotein-rich lipid bilayer. Non-infectious L-particles are composed mainly of envelope and tegument proteins and are devoid of capsids and viral DNA. L-particles were first described in the early nineties and from then on investigated for their formation and role during virus infection. The development and secretion of L-particles occur simultaneously to the assembly of complete viral particles. HSV L-particles are assembled by budding of condensed tegument into Golgi-delivered vesicles and are capable of delivering their functional content to non-infected cells. Thereby, HSV L particles contribute to viral pathogenesis within the infected host by enhancing virion infectivity and providing immune evasion functions. In this review we discuss the emergence of HSV-1 L-particles during virus replication and their biological functions described thus far.